Flourishing and Well-being in the Academy: A Capabilities Approach - Gereluk, Dianne (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2018)
Increased wellness and mental health strategies have been implemented across campuses in post-secondary institutions, which is reflective of the broader discourse on wellness in societies.  In response to increased awareness of wellness on campuses, universities respond in various ways which include student and staff engagement surveys, academic plans that include wellness, and institutional mental health strategies.  While these initiatives are important to support the communities that universities serve, such initiatives may do better if a more robust notion of wellbeing underpins these initiatives.  In this paper, I draw upon Nussbaum’s capabilities to broaden the discourse on wellbeing in academia.  I argue that considering wellbeing through a capabilities approach may provide a better normative framework to address more substantive tensions that undermine academics’ well-being.